Evaluation of the Pattern of the Commercial Relationship between the Ginger Farmers and the Middlemen in Southern Kaduna, Nigeria - Isaac, John; Kao’je , Umar Abdullahi; Moveh, David (Kashere Journal of Politics and International Relations, 2025)
This study explored the commercial relationship between ginger farmers and middlemen in Nigeria, focusing on the extent and nature of their interactions. Data were collected through a descriptive survey using questionnaires from a sample of 397 respondents. The findings revealed that middlemen enforce quality standards and provide guidance on post-harvest handling to ensure ginger meets market expectations. They manage negotiations and resolve disputes related to pricing, quality, and contracts. In addition, middlemen offer credit or advances for seeds and fertilizers to help farmers manage cash flow before harvest and facilitate access to larger markets and distribution networks. The study recommends government support for initiatives that formalize and regulate the roles of middlemen in the ginger trade, as well as NGO support for financial services to enhance the capabilities of ginger farmers, such as providing access to credit or advances for inputs like seeds and fertilizers.